Kemampuan Kreativitas dan Literasi Sains dengan Membuat Daur Hidup Hewan Siswa Kelas IV SDN 2 Sukamaju - Sifa Aulia Rachman; Risma Listiani; Husnul Khatimah Khatimah; Yunike Berry; Yuni Astuti Tri Tartiani (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2022)
This dedication is motivated by the creativity and scientific literacy abilities of students at SDN 2 Sukamaju, since the distance learning system has created new problems, especially in the world of education. The quality of school resources, parental resources, online media, and internet access do not support the learning process, causing children here to find it difficult to understand school subject matter. The problem of the ability of creativity and scientific literacy should not be left without efforts to deal with the problem because the nation's children are the hope and successor in a prosperous future of Indonesia. In dealing with this, the Minister of Education and Culture, Nadiem Makarim, provided opportunities for students in the Campus Teaching Program Batch 2 to assist in school administration, technology adaptation, and improving literacy and numeracy in schools. The object of this service activity is the fourth grade students of SDN 2 Sukamaju which is located in Pugeran Village, Sukamaju Village, Bantarkalong District, Tasikmalaya Regency, West Java Province which involves 21 students. This service aims to help solve problems, upgrade, and provide understanding to students regarding the ability of creativity and scientific literacy. The method of this activity is by observing, socializing, delivering material and direct practice to students. The results of this service activity are the fourth grade students of SDN 2 Sukamaju, the ability of creativity and scientific literacy, especially in the Animal Life Cycle and Cycle material, there is an increase. Key Words: Creativity Ability; Science Literacy; Campus Teaching Program